Grey linear regression model and its application - Xinping Xiao; Yayun Lu (Proceedings of 2011 IEEE International Conference on Grey Systems and Intelligent Services, 2011)
The parameter estimation computation in grey linear regression model is relatively complicated, the development coefficient is decided by its simple average and it's vulnerable with the aberrant value and logarithmic neck may be negative. Aiming at those problems, in this paper, we present a new estimation method and three kinds of representations of the model including the Range form, Connotation form and Differential form, then, we obtain the relationship between Connotation form and Differential form, and also get the relationship between the model and GM(1,1) model. Finally an application of short-term traffic flow prediction based on the model is given and some good effects have been achieved.